Magnetic resonance imaging : physical principles and sequence design - Brown, Robert W., 1941-; Cheng, Yu-Chung N.; Haacke, E. Mark.; Thompson, Michael R.; Venkatesan, Ramesh (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
New edition explores contemporary MRI principles and practices Thoroughly revised, updated and expanded, the second edition of Magnetic Resonance Imaging: Physical Principles and Sequence Design remains the preeminent text in its field. Using consistent nomenclature and mathematical notations throughout all the chapters, this new edition carefully explains the physical principles of magnetic resonance imaging design and implementation. In addition, detailed figures and MR images enable readers to better grasp core concepts, methods, and applications. Magnetic Resonance Imaging, Second Edition
Preceded by Magnetic resonance imaging : physical principles and sequence design / E. Mark Haacke ... [et al.]. c1999.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Magnetic Resonance Imaging; Nuclear magnetic resonance; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Nuclear magnetic resonance; Magnetic resonance imaging; Magnetic Resonance Imaging; Physical Phenomena; Electronic books